2022
DOI: 10.3758/s13423-022-02108-x
|View full text |Cite
|
Sign up to set email alerts
|

Symbolic number comparison and number priming do not rely on the same mechanism

Abstract: In elementary symbolic number processing, the comparison distance effect (in a comparison task, the task is more difficult with smaller numerical distance between the values) and the priming distance effect (in a number processing task, actual number is easier to process with a numerically close previous number) are two essential phenomena. While a dominant model, the approximate number system model, assumes that the two effects rely on the same mechanism, some other models, such as the discrete semantic syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In the present study, the absence of correlation between the comparison implicit-DE and the comparison explicit-DE further supports the involvement of different cognitive processes such as long-and shortterm memory retrieval. Previous studies have already shown that the comparison DE does not correlate with either the priming DE (Krajcsi & Szűcs, 2022;Van Opstal et al, 2008) or the reverse DE (Goffin & Ansari, 2016;Vogel et al, 2021). This opens the question of whether it is more appropriate to discuss the DE in terms of flexibility of a single effect, or to talk about different effects related to the same property (the numerical distance).…”
Section: Explicit-and Implicit-desmentioning
confidence: 97%
See 1 more Smart Citation
“…In the present study, the absence of correlation between the comparison implicit-DE and the comparison explicit-DE further supports the involvement of different cognitive processes such as long-and shortterm memory retrieval. Previous studies have already shown that the comparison DE does not correlate with either the priming DE (Krajcsi & Szűcs, 2022;Van Opstal et al, 2008) or the reverse DE (Goffin & Ansari, 2016;Vogel et al, 2021). This opens the question of whether it is more appropriate to discuss the DE in terms of flexibility of a single effect, or to talk about different effects related to the same property (the numerical distance).…”
Section: Explicit-and Implicit-desmentioning
confidence: 97%
“…In this view, both the comparison and the priming DE are different aspects of the ratio effect arising at the semantic processing stage: The fact that the distributions of close numbers (e.g., 4 and 5) overlap more than the distributions of far numbers (e.g., 1 and 5) would lead to faster discrimination between far numbers in comparison tasks, and to faster coactivation of close numbers in priming tasks (Koechlin et al, 1999). However, dissociations and null correlations between the comparison and the priming DE (Krajcsi & Szűcs, 2022;Turconi et al, 2006) have challenged this account and suggested others which emphasize the role of response-related processing in the emergence of the DE.…”
Section: Theoretical Accounts Of the Dementioning
confidence: 99%
“…Considering both factors, in some cases, it is not easy to find an appropriate compromise, or it may be impossible to find an appropriate solution: For some indices, it is possible that no reliable measurement can be designed, and it may be impossible to measure the individual differences of some abilities appropriately (see a similar failure even in adults in . In some other cases, a reliable index requires so many trials (e.g., 13,400 trials for an appropriate priming distance effect index in adults; Krajcsi & Szűcs, 2022) that it cannot be achieved with child participants. Note that it is not only the reliability of the indices that may be compromised by the small number of trials but also the precision of the reliability 16/32 measurements (i.e., the reliability index may be noisy or, in other words, may not be reliable).…”
Section: Consider Reliabilitymentioning
confidence: 99%